Percutaneous tibial nerve stimulation vs sacral nerve stimulation for faecal incontinence: a comparative case‐matched study. (November 2014) - Al Asari, S.; Meurette, G.; Mantoo, S.; Kubis, C.; Wyart, V.; Lehur, P.‐A.
Abstract Aim The study assessed the initial experience with posterior tibial nerve stimulation (PTNS) for faecal incontinence and compared it with sacral nerve stimulation (SNS) performed in a single centre during the same timespan. Method A retrospective review of a prospectively collected database was conducted at the colorectal unit, University Hospital, Nantes, France, from May 2009 to December 2010. Seventy‐eight patients diagnosed with chronic severe faecal incontinence underwent neurostimulation including PTNS in 21 and SNS in 57. The main outcome measures were faecal incontinence (Wexner score) and quality of life (Fecal Incontinence Quality of Life, FIQL) scores in a short‐term follow‐up. Results No significant differences were observed in patients' characteristics. Of 57 patients having SNS, 18 (32%) failed peripheral nerve evaluation and 39 (68%) received a permanent implant. Two (5%) developed a wound infection. No adverse effects were recorded in the PTNS group. There was no significant difference in the mean Wexner and FIQL scores between patients having PTNS and SNS at 6 (P = 0.39 and 0.09) and 12 months (P = 0.79 and 0.37). A 50% or more improvement in Wexner score was seen at 6 and 12 months in 47% and 30% of PTNS patients and in 50% and 58% of SNS patients with no significant difference between the groups. Conclusion Posterior tibial nerve stimulation is a valid method of treating faecal incontinence in the short term when conservative treatment has failed. It is easier, simpler, cheaper and less invasive than SNS with a similar short‐term outcome.